Science Fun: Theory of Light - Saidatul Khoiriyah; Adhelia Karunia Sukma (Indonesia Approach Education, 2020)
We as budding researchers, try to present science in the form of comics. We present the theory of light by Christiaan Huygens and Sir Isaac Newton in a short comic strip.